The genealogy and heraldry of the noble families of Malta - Gauci, Charles A. (Valletta : Gulf, 1981)
The rulers of Malta - The grand feudal Lords of Malta - The Maltese nobility - The Marquises, the Counts and the Barons - Royal connections of the Maltese nobility - Maltese titles disposable by nomination - Titels since october 1981 - Extinct Magistral titels - Patal titels granted to Maltes citizens - Royal connections - Some families of historical interest - Foreign titels in Malta
Keywords: Adel -- Malta